THE INFLUENCE OF PROBLEM BASED LEARNING MODEL TOWARD SAINS LITERACY ‎SKILL OF STUDENT ON REACTION RATE MATERIALS - Dede Fitriani; burhanudin milama; dedi irwandi (Faculty of Education and Teacher Training, UIN (State Islamic University) Syarif Hidayatul, 2017)
This study was aimed to know the effect of problem-based learning model on the ability of students scientific literacy in reaction rate material. Scientific literacy that is examined in this study only on competency dimension of science. This research was conducted at SMAN 8 South TangerangCity. The method used was quasi-experimental with nonequivalent control group design. The sample was taken byusing purposive sampling technique. The data was taken by using an essay test of scientific literacy ability in competency dimension of science. The analysis of data used is t-test that obtained tcountvalue totaled 8.27 and ttable on significant level0.05is 1.99, so that thetcount>ttable. So we can concludethat Ho was refuse. This indicatesthatthe application of problem-based learning model provides a significant impact on the ability of students scientific literacy in reaction rate material. Keywords: Problem Based Learning Model; Scientific Literacy; Competency Dimension of Science; reaction Rate.